2020
DOI: 10.1007/s11845-020-02289-1
|View full text |Cite
|
Sign up to set email alerts
|

Intense remodeling of extracellular matrix within the varicose vein: the role of gelatinases and vascular endothelial growth factor

Abstract: Background Increased blood pressure in the varicose veins (VV) can contribute to the overexpression of matrix metalloproteinases (MMPs), affecting the endothelium, smooth muscle, and extracellular matrix of the vein wall. Gelatinases (MMP-2 and MMP-9), hypoxia, and inflammation occurring in the VV wall contribute to the increased expression of vascular endothelial growth factor (VEGF). Aims Our objective was to analyze the concentration of gelatinases and VEGF in the great saphenous VV wall and plasma of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…VEGF is the major inducer of angiogenesis in a variety of in vivo models and plays an essential role in numerous physiological and Evidence-Based Complementary and Alternative Medicine pathological processes, including angiogenesis and immune response [26,27]. Increased expression of VEGF has been reported to alleviate endometrium injury in a wounded rat uterus [28]. e patients with IUA showed vascular closure in endometrial tissues and had significantly increased VEGF expression after therapy, suggesting angiogenesis in the endometrial tissues may affect the endometrial repair [29].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is the major inducer of angiogenesis in a variety of in vivo models and plays an essential role in numerous physiological and Evidence-Based Complementary and Alternative Medicine pathological processes, including angiogenesis and immune response [26,27]. Increased expression of VEGF has been reported to alleviate endometrium injury in a wounded rat uterus [28]. e patients with IUA showed vascular closure in endometrial tissues and had significantly increased VEGF expression after therapy, suggesting angiogenesis in the endometrial tissues may affect the endometrial repair [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the regulation of voltage dependent Ca 2+ channels is altered with aging processes and hence affects vascular function [ 218 ]. Furthermore, some studies reported that primary VV show aberrant release of VEGF, which, in combination with other altered molecules, might increase the permeability of venous wall, allowing the infiltration of inflammation markers [ 219 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In Varizen wurden MMP-1, -2, -3, -7, -9 und -13 untersucht. In Varizen wurde eine Überexpression von MMP-9 im Zusammenhang mit einem erhöhten Gehalt an vaskulärem endothelialem Wachstumsfaktor (VEGF) festgestellt [10]. VEGF ist ein Molekül (Wachstumsfaktor), das von verschiedenen Zellen produziert wird (Thrombozyten, Makrophagen, Mesangiumzellen der Niere usw.…”
Section: Extrazelluläre Matrix Der Venenwandunclassified
“…MMP-1, -2, -3, -7, -9 and -13 have been studied in varicose veins. Overexpression of MMP-9 was found in varicose veins, with a positive correlation with elevated levels of vascular endothelial growth factor (VEGF) [10]. VEGF is a molecule (a grow factor) produced by several cells (platelets, macrophages, renal mesangial cells, etc.)…”
Section: Extracellular Matrix Of the Vein Wallmentioning
confidence: 99%